PENGARUH LINGKUNGAN SOSIAL DAN SIKAP REMAJA TERHADAP PERUBAHAN TATA NILAI - Pitoewas, Berchah (JPK (Jurnal Pancasila dan Kewarganegaraan), 2018)
Based on interviews to custom character, the author identifying there is a change of values in the village of Tanjung Harapan, Seputih Banyak Central Lampung Regency. The community used to be acquainted with local values and can run these values, now this value has already started to fade. The community began living individual in the association. This research aims to know the influence of the social environment and teen attitudes toward change values in the village of Tanjung Harapan , Seputih Banyak Central Lampung Regency. Research methods using quantitative descriptive. Data collection techniques using question form. Data processing used formula Product Moment, which is then followed by the formula Sperman Brown.Based on the results of the research that has been conducted on the influence of the social environment and Teen Attitudes toward Change Values in the village of Tanjung Harapan ,Seputih Banyak Central Lampung Regency, then it can be inferred that there is an influence significantly between attitudes towards social and environmental values. The social environment has a role as a vehicle of non formal education in the framework of the establishment of the attitude of adolescents in associating and communicating